Influenceable and Avoidable Risk Factors for Systemic Air Embolism due to Percutaneous CT-Guided Lung Biopsy: Patient Positioning and Coaxial Biopsy Technique—Case Report, Systematic Literature Review, and a Technical Note - Gernot Rott; Frieder Boecker (Radiology Research and Practice)
Following the first case of a systemic air embolism due to percutaneous CT-guided lung biopsy in our clinic we analysed the literature regarding this matter in view of influenceable or avoidable risk factors. A systematic review of literature reporting cases of systemic air embolism due to CT-guided lung biopsy was performed to find out whether prone positioning might be a risk factor regarding this issue. In addition, a technical note concerning coaxial biopsy practice is presented. Prone position seems to have relevance for the development and/or clinical manifestation of air embolism due to CT-guided lung biopsy and should be considered a risk factor, at least as far as lesions in the lower parts of the lung are concerned. Biopsies of small or cavitary lesions in coaxial technique should be performed using a hemostatic valve.